Edutainment-Based Learning Model with Powerpoint Media Enhancing Students’ Learning Motivation - Susilawati S., C. Lenny; Suyanto, Suyanto; Gufron, Anik (Universitas Pendidikan Ganesha, 2021)
The low student learning motivation, especially in the elementary level, is influenced by outdated learning media. This study aims at improving students’ learning motivation in social sciences among fifth-grade students through an edutainment-based learning model with PowerPoint. This research employed Classroom Action Research adapting Kemmis and Taggart model. The object of this research was the social sciences in Elementary School. The data collection techniques were through direct observation, questionnaires, and interviews. This research was conducted in two cycles and the improvements were made in the form of learning strategies in each cycle. The results showed that the learning process of social sciences using the developed PowerPoint could improve the students’ learning motivation among the fifth-grade students of the elementary school in the social sciences subject. Based on the observation results before the study, the average percentage was 60.00% or in the moderate category. After the research was carried out, it became 76.67% for the first cycle, and 88.33% or in the high category for the second cycle, respectively. The questionnaire results before the study were 55.08% or in the moderate category. After the learning process with the developed PowerPoint, it increased to 73.31% in the first and 81.37% in the high category in the second cycle, respectively. It indicates that the use of the developed learning media can significantly enhance students’ learning motivation among the students at elementary school.